Pengaruh Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Studi Pada PT Elharamain Wisata - Adeng Mutawakil Alallah; Arini Fitria Mustapita; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study examines the influence of work motivation, work discipline, and work environment on employee performance at PT Elharamain Wisata. The research was conducted using a quantitative approach with a survey method. The population consisted of all employees of PT Elharamain Wisata, and a saturated sampling technique was applied, involving 35 respondents. Data were collected through structured questionnaires that had passed validity and reliability testing. The analysis employed multiple linear regression, supported by classical assumption tests, as well as simultaneous (F-test) and partial (t-test) hypothesis testing. The findings indicate that work motivation, work discipline, and work environment simultaneously have a significant effect on employee performance. Partially, each independent variable also demonstrates a positive and significant influence on performance. These results suggest that higher levels of motivation, stronger discipline, and a more conducive work environment contribute to improved employee performance. This study highlights the importance of integrated human resource management strategies, particularly in service-based companies operating in a competitive religious travel industry. The results provide practical implications for management in enhancing employee productivity and service quality, while also contributing to the development of human resource management literature. Keywords Work Motivation, Work Discipline, Work Environment, Employee Performance, Human Resource Management, PT Elharamain Wisata.